Malay students patterns of social interaction with special reference to Malay students at Northern Illinois University (De Kalb). - Abdullah Taib (Universiti Kebangsaan Malaysia, 1979)
This paper attempts to show that differences in cultural norms and values resulted in little interaction between Malay and American students. Theoretically, Northern Illinois University (NIU) provides a high interaction potential, in view of the size of the university and of the city. NIU is a medium sized university located in a small city. Despite this fact, Malay students on the campus only interacted amongst themselves. The reluctance and unwillingness of Malay students to interact with Americans are due to the fact that they consider the American way of life a threat to their way of life. American cultural norms and values are in direct contrast to Malay cultural norms and values. It is in order to avoid "contamination" by this culture that caused Malay students to withdraw from participating in American life.